CSS3 for dummies - Mueller, John, 1958- (Hoboken, NJ : John Wiley & Sons, Inc., 2014)
CSS3 is loaded with features like better mobility, cleaner code, and less maintenance. Learn to use CSS3 shortcuts; work with fonts, colors, and graphics; customize the interface with jQuery UI; and more.
Includes index.
Keywords: Cascading style sheets; Web sites -- Design